2007
DOI: 10.1136/jnnp.2006.112037
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cluster headache: a French clinical descriptive study

Abstract: Background: Cluster headache (CH) is a relatively rare disease and episodic CH is more frequent than chronic CH. Few studies have described the characteristics of patients with chronic CH. Methods: This was a descriptive study carried out by eight tertiary care specialist headache centres in France participating in the Observatory of Migraine and Headaches (OMH). From 2002 to 2005, OMH collected data from 2074 patients with CH, of whom 316 had chronic CH. From January to June 2005, 113 patients with chronic CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
143
7
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(173 citation statements)
references
References 28 publications
18
143
7
5
Order By: Relevance
“…At first glance, these findings seem in line with the well-documented abuse of nicotine (80% smokers as compared to 35% in the general population) (2), relatively high coffee consumption and the finding that 26% of cluster patients regularly use cannabis (3). There are conflicting data regarding alcohol consumption, with clinicians and smaller studies reporting significant abuse and a recent study by Schu¨rks et al, who report the opposite (4).…”
supporting
confidence: 61%
“…At first glance, these findings seem in line with the well-documented abuse of nicotine (80% smokers as compared to 35% in the general population) (2), relatively high coffee consumption and the finding that 26% of cluster patients regularly use cannabis (3). There are conflicting data regarding alcohol consumption, with clinicians and smaller studies reporting significant abuse and a recent study by Schu¨rks et al, who report the opposite (4).…”
supporting
confidence: 61%
“…Consistent with the findings from previous studies,3, 4, 13 the most frequent aura symptoms were visual, which in our study started in most cases prior to the headache. Dysarthria and dysphasia, most often during the headache phase, was reported by 27.3% and 22.7% participants, respectively, which seems much higher than the 4.5%–8% reported in previous studies 2, 4, 5, 13…”
Section: Discussionsupporting
confidence: 93%
“…Dysarthria and dysphasia, most often during the headache phase, was reported by 27.3% and 22.7% participants, respectively, which seems much higher than the 4.5%–8% reported in previous studies 2, 4, 5, 13…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…There also have a report that drug induced headaches are affiliated with anxiety [30]. Another study has been found that 43% in patients with chronic cluster headache had higher depression scores than those who did not [31]. Moreover, there have been reports patients with anxiety and depression were frequently observed to have chronic daily headaches [32].…”
Section: Discussionmentioning
confidence: 99%